2012
DOI: 10.2460/javma.240.12.1474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chlamydophila psittaci infection and other risk factors for atherosclerosis in pet psittacine birds

Abstract: Infection with C psittaci and a high plasma cholesterol concentration may be risk factors for developing atherosclerosis in pet psittacine birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…It most frequently infects Psittaciformes but can also infect many other avian species, as well as a wide range of mammalian hosts (Kaleta and Taday, 2003;Zhu et al, 2013). The highest infection rates are identified in psittacine birds and pigeons (Donham and Zejda, 1992;Pilny et al, 2012). It can infect humans by inhalation or close contact (Beeckman and Vanrompay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It most frequently infects Psittaciformes but can also infect many other avian species, as well as a wide range of mammalian hosts (Kaleta and Taday, 2003;Zhu et al, 2013). The highest infection rates are identified in psittacine birds and pigeons (Donham and Zejda, 1992;Pilny et al, 2012). It can infect humans by inhalation or close contact (Beeckman and Vanrompay, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…46,47 In fact, these effects could well be reversed in female birds, for which estrogens have tremendous physiologic effects on lipid, protein, and calcium metabolism related to reproduction and egg formation. 4,6,17,42 The reasons for this are unknown, but one can speculate that these genera may have physiologic and genetic differences or different captive lifestyle and stress levels that could influence atherogenesis. 48,49 Increased plasma cholesterol, very low-density lipoprotein, very low-densitylipoprotein remnants, and non-high-density lipoprotein cholesterol concentrations promote atherogenesis, providing a plausible explanation for the enhanced predisposition found in female psittacine birds.…”
Section: Discussionmentioning
confidence: 99%
“…10 Lipid-lowering therapeutic agents are being used extensively in both prevention and treatment of atherosclerosis in humans. [14][15][16] In addition, studies of avian models of atherosclerosis consistently showed an increased blood total and LDL cholesterol values, but the dyslipidemia was artificially induced by high-cholesterol feeding. 11 Unfortunately, when there is no pub-lished scientific or pharmacologic information available regarding statin use in pet birds, avian veterinarians have to resort to the empirical use of these drugs.…”
Section: Introductionmentioning
confidence: 99%